Variations in outcomes for Indigenous women with breast cancer in Australia: A systematic review. (10th February 2017) - Dasgupta, P.; Baade, P.D.; Youlden, D.R.; Garvey, G.; Aitken, J.F.; Wallington, I.; Chynoweth, J.; Zorbas, H.; Roder, D.; Youl, P.H.
Abstract : This systematic review examines variations in outcomes along the breast cancer continuum for Australian women by Indigenous status. Multiple databases were systematically searched for peer‐reviewed articles published from 1 January 1990 to 1 March 2015 focussing on adult female breast cancer patients in Australia and assessing survival, patient and tumour characteristics, diagnosis and treatment by Indigenous status. Sixteen quantitative studies were included with 12 rated high, 3 moderate and 1 as low quality. No eligible studies on referral, treatment choices, completion or follow‐up were retrieved. Indigenous women had poorer survival most likely reflecting geographical isolation, advanced disease, patterns of care, comorbidities and disadvantage. They were also more likely to be diagnosed when younger, have advanced disease or comorbidities, reside in disadvantaged or remote areas, and less likely to undergo mammographic screening or surgery. Despite wide heterogeneity across studies, an overall pattern of poorer survival for Indigenous women and variations along the breast cancer continuum of care was evident. The predominance of state‐specific studies and small numbers of included Indigenous women made forming a national perspective difficult. The review highlighted the need to improve Indigenous identification in cancer registries and administrative databases and identified key gaps notably the lack of qualitative studies in current literature.